A non-obese, diet-induced animal model of nonalcoholic steatohepatitis in Wistar/ST rats compared to Sprague-Dawley rats. (April 2020) - Omagari, Katsuhisa; Suzuta, Masako; Taniguchi, Asami; Kumamoto, Risa; Koyama, Yuko; Fukuda, Ayumi; Suruga, Kazuhito; Ichimura-Shimizu, Mayuko; Tsuneyama, Koichi
Summary: Background: Non-alcoholic steatohepatitis (NASH), a subtype of non-alcoholic fatty liver disease (NAFLD), is a potentially progressive liver disease that can lead to cirrhosis. Obesity increases the risk of NAFLD/NASH, but this disease can also be observed in non-obese individuals. Methods: We investigated the metabolic and histopathological changes in 13 obesity-resistant Slc:Wistar/ST rats fed a high-fat and high-cholesterol (HFC) diet for 9 weeks, and also retrospectively compared the results of 41 Sprague-Dawley (SD) rats that were previously fed with the same protocol to the results of the Slc:Wistar/ST rats. Results: Of the 13 Slc:Wistar/ST rats fed an HFC diet containing 1.25% or 2.5% cholesterol, 11 (84.6%) developed histologically proven NASH without obesity, an increased visceral fat volume, insulin resistance, histopatological severe lobular inflammation and severe hepatic fibrosis. The HFC diets significantly increased the levels of mRNA encoding collagen type I alpha 1 (COL1A1), transforming growth factor-β1 (TGF-β1), tumor necrosis factor-α (TNF-α) and monocyte chemoattractant protein-1 (MCP-1). The SD rats also developed NASH without obesity, an increased visceral fat volume and insulin resistance, but the metabolic and histopathological effects, such as lower serum adiponectin levels, higher serum leptin levels, histopatological severe lobular inflammation and hepatic fibrosis, seemed to be more pronounced in the SD rats than in the Slc:Wistar/ST rats. Conclusions: These two rat models may reflect the human etiology of NASH that is influenced by dietary factors, and the obesity-resistant Slc:Wistar/ST rat model may be particularly useful for elucidating the pathophysiological mechanism of the so-called "lean NASH".